2014
DOI: 10.1016/j.compositesa.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Wool fibres functionalised with a silane-based coupling agent for reinforced polypropylene composites

Abstract: Polypropylene (PP)-based composites containing 20 wt.% wool fibres were successfully prepared using a simple melt blending procedure. A blend of a commercial-grade PP and a maleinised PP was chosen as the matrix. To investigate the effects of modifying the fibre surface on the fibre/matrix adhesion, wool fibres were used as received, oxidised, or functionalised with a silane-based coupling agent, capable in principle of reacting with both the fibres and the polyolefinic matrix. The silanisation of the fibres a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Figure (d) suggests that nanofiber whiskers with a certain aspect ratio formed a three‐dimensional network structure in which the whiskers were surrounded by voids; this indicated the presence of elastomers with a certain thickness. Similar structures have been reported in the literature . Combined with the FTIR spectroscopy of the POE–NCWs, this further demonstrated that the POE–NCWs could form a high‐intensity interfacial layer with an elastomeric matrix by covalently linking the elastomeric flexible long‐chain molecules to effectively prevent separation from the elastomeric matrix in the melting process, even under extremely high temperatures and larger shear forces.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Figure (d) suggests that nanofiber whiskers with a certain aspect ratio formed a three‐dimensional network structure in which the whiskers were surrounded by voids; this indicated the presence of elastomers with a certain thickness. Similar structures have been reported in the literature . Combined with the FTIR spectroscopy of the POE–NCWs, this further demonstrated that the POE–NCWs could form a high‐intensity interfacial layer with an elastomeric matrix by covalently linking the elastomeric flexible long‐chain molecules to effectively prevent separation from the elastomeric matrix in the melting process, even under extremely high temperatures and larger shear forces.…”
Section: Resultssupporting
confidence: 85%
“…Now, several studies of NCWs reinforcing PP have appeared in the literature . We developed a unique way to re‐treat NCWs and also successfully blended them with PP to improve their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking and dehydration tendency of sulphur-containing amino acids in wool can improve char formation under combustion, making wool fibres not melting and dripping [8]. Recently, some researchers have investigated the fabrication and properties of wool based thermoplastic composites [9,10] but the reported mechanical properties, especially tensile strengths, have been poor compared to those of neat PPs. To overcome this problem, the authors have performed a systematic study on PP-wool composites [11,12] and have succeeded in achieving improved mechanical properties.…”
Section: Introductionmentioning
confidence: 97%
“…However, a great challenge regarding its use in the plastics industry is the fact that most resins, such as polyethylene (PE) and polypropylene (PP), are nonpolar (hydrophobic), while NCC is highly polar (hydrophilic) thus leading to compatibility problems . To improve compatibility between NCC and nonpolar polymers, different methods such as surface modification, polymer grafting, surfactants, and coupling agents have been studied. Although some studies on PP‐NCC nanocomposites can be found in the literature none of them used extrusion (melt blending) to compound their materials.…”
Section: Introductionmentioning
confidence: 99%
“…To improve compatibility between NCC and nonpolar polymers, different methods such as surface modification, polymer grafting, surfactants, and coupling agents have been studied. Although some studies on PP‐NCC nanocomposites can be found in the literature none of them used extrusion (melt blending) to compound their materials. Extrusion of nanocomposites is very important since PP is most commonly processed and compounded via extrusion.…”
Section: Introductionmentioning
confidence: 99%